2015
DOI: 10.1007/s12155-015-9586-1
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Tillage Management Affect Corn Cellulosic Yield, Composition, and Ethanol Potential

Abstract: Corn (Zea mays L.) stover and cobs remaining after grain harvest can serve as a feedstock for cellulosic ethanol production. Field trials were conducted at two locations in Minnesota over three years to determine how corn cellulosic yield composition and ethanol yield are influenced by tillage system [chisel tillage (CT), strip-tillage (ST), and no-tillage (NT)] and fertilizer N rate (0, 45, 90, 134, 179, and 234 kg N ha −1 ). Stover biomass yield, C and N concentrations and content, and potential ethanol yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This increase in lignin concentration is significant as it negatively impacts the cell wall's degradability, thereby affecting hydrolysis efficiency, which is essential for converting biomass to ethanol [40]. Sindelar et al [41] observed a linear decrease in theoretical ethanol yield from corn stover with increased N fertilizer, by 0.07 to 0.10 L Mg −1 for every 1 kg N ha −1 increase in N fertilization. However, theoretical ethanol yields of cobs were unaffected by N fertilization and were reported to be 9 to 20% higher than stover when averaged across N fertilizer rates.…”
Section: Agronomic Practices On Corn Stover Quality and Biofuel Poten...mentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in lignin concentration is significant as it negatively impacts the cell wall's degradability, thereby affecting hydrolysis efficiency, which is essential for converting biomass to ethanol [40]. Sindelar et al [41] observed a linear decrease in theoretical ethanol yield from corn stover with increased N fertilizer, by 0.07 to 0.10 L Mg −1 for every 1 kg N ha −1 increase in N fertilization. However, theoretical ethanol yields of cobs were unaffected by N fertilization and were reported to be 9 to 20% higher than stover when averaged across N fertilizer rates.…”
Section: Agronomic Practices On Corn Stover Quality and Biofuel Poten...mentioning
confidence: 99%
“…However, theoretical ethanol yields of cobs were unaffected by N fertilization and were reported to be 9 to 20% higher than stover when averaged across N fertilizer rates. The authors stated that "variation in stover feedstock quality and ethanol output is possible as a result of the interactive effects among management, genetics, and temporal and spatial environmental variation" and "that cobs may be a more viable option for cellulosic ethanol production", taking N fertilization into account [41].…”
Section: Agronomic Practices On Corn Stover Quality and Biofuel Poten...mentioning
confidence: 99%